Regulatory T Cells: Angels or Demons in the Pathophysiology of Sepsis? - Gao, Yu-lei; Yao, Ying; Zhang, Xiang; Chen, Fang; Meng, Xiang-long; Chen, Xin-sen; Wang, Chao-lan; Liu, Yan-cun; Tian, Xin; Shou, Song-tao; Chai, Yan-fen (Frontiers in Immunology, 2022)
Sepsis is a syndrome characterized by life-threatening organ dysfunction caused by the dysregulated host response to an infection. Sepsis, especially septic shock and multiple organ dysfunction is a medical emergency associated with high morbidity, high mortality, and prolonged after-effects. Over the past 20 years, regulatory T cells (Tregs) have been a key topic of focus in all stages of sepsis research. Tregs play a controversial role in sepsis based on their heterogeneous characteristics, complex organ/tissue-specific patterns in the host, the multi-dimensional heterogeneous syndrome of sepsis, the different types of pathogenic microbiology, and even different types of laboratory research models and clinical research methods. In the context of sepsis, Tregs may be considered both angels and demons. We propose that the symptoms and signs of sepsis can be attenuated by regulating Tregs. This review summarizes the controversial roles and Treg checkpoints in sepsis.